Reductions in sexually transmitted infections associated with popular opinion leaders in China in a randomised controlled trial. Issue 4 (29th January 2011) - Rotheram-Borus, Mary Jane; Wu, Zunyou; Liang, Li-Jung; Li, Li; Detels, Roger; Guan, Jihui; Yin, Yueping; Swendeman, Dallas
Abstract : Objectives: A community level randomised controlled trial of a Community Popular Opinion Leader (C-POL) intervention to reduce bacterial and viral sexually transmitted infections (STIs) and unprotected extramarital sex was carried out over 2 years in five countries. The main study results did not find significant intervention effects. This paper presents a sub-analysis examining the differential intervention impacts among high-risk and low-risk participants in the China site. Methods: From 2002 –2006, 3912 migrant market vendors aged 18 and 49 years were recruited at an urban site in China. Markets were randomly assigned to the C-POL intervention (N=20 markets; n=1979) or standard-care control condition (N=20; n=1933). Both study condition venues received HIV/STI education, free condoms, STI testing and treatment, and training for pharmacists in antibiotic treatments. In intervention markets, C-POLs were identified and trained to diffuse messages regarding safer sex, STI treatment and partner discussions of sex. The primary biological outcome was incidence of new STIs (chlamydia, gonorrhoea, syphilis, trichomonas, herpes or HIV). The primary sexual behaviour risk outcome was any unprotected extramarital sex in the prior 3 months. Results: In unadjusted analyses, women had significantly lower rates of STI infection at 24 months in the C-POL intervention (5.7%) compared to controls (8.3%; p=0.043). In mixed-effects regression models, intervention participants with STIs at previous assessments were about half as likely to have STIs at 24 months (OR 0.47, 95% CI 0.25 to 0.90) compared to controls. Conclusions: The C-POL intervention lowers HIV risk among those at highest risk (ie, with a STI or engaging in high-risk sexual activities) rather than the general population. Trial registration: http://Clinicaltrials.gov/ identifier NCT 00710060.